Perancangan Mesin Perontok Tandan Buah Kelapa Sawit Yang Restan - Febrianton, Adi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Threshing is the post-harvest handling stage after the harvesting process. Threshing is an integral part of the palm post-harvest handling process. The harvested oil palms are threshed to separate the fruit from the bunches. The threshing process is carried out so that small oil palm fruits or oil palm fruit bunches weighing below 5 kg can be accepted at the palm oil mill. Generally, the weight of fresh fruit bunches (FFB) under 5 kilograms is not sold, so before being taken to the palm oil mill, it must be threshed first so that the palm oil becomes brondolan or grains of palm oil that can be accepted by the palm oil mill. In this final project, the author designed a small oil palm fruit threshing machine from the bunches aimed at increasing the profits of farmers or oil palm entrepreneurs, because small oil palm fruits can be accepted at palm oil mills. In this design, the driving engine uses a fuel motor motor with a power of 7 HP.